Target Registration Error minimization involving deformable organs using elastic body splines and Particle Swarm Optimization approach. (December 2017) - Spinczyk, Dominik; Fabian, Sylwester
Abstract: In minimally invasive surgery one of the main challenges is the precise location of the target during the intervention. The aim of the study is to present usability of elastic body splines (EBS) to minimize TRE error. The method to find the desired EBS parameters values is presented with usage of Particle Swarm optimization approach. This ability of TRE minimization has been achieved for the respiratory phases corresponding to minimum FRE for abdominal (especially liver) surgery. The proposed methodology was verified during experiments conducted on 21 patients diagnosed with liver tumors. This method has been developed to perform operations in real-time on a standard workstation. Graphical abstract: Highlights: Minimization of Target Registration Error for minimally invasive intervention was achieved. Usability of elastic body splines to minimize Target Registration Error was presented. Particle Swarm optimization approach was used to find parameters of spline curves.